Craque para o futuro: políticas sociais, educação e esporte em Soure-Pará-Brasil - CONCEIÇÃO, Marcos Adrian Macêdo (2022)
This Course Conclusion Work sought to understand the relevance of the “Craque para o futuro” project, as a social sports action for children based in the region of Marajó Oriental, municipality of Soure, as well as to investigate whether it meets its proposed objectives, based on the studies learned in the teaching of Human Geography. It also sought to identify whether there are contradictions between the facts and to verify the relevance that this project brings in the perception of those responsible for the children and adolescents. Methodologically, interviews were carried out with all those involved in the project and the data were analyzed through the definition of categories. The main theoretical elements were involved in the conception of Law Social and Social Legislation, present in the work of Leonice Aparecida de Fátima Alves, “(...)”. It was analyzed to dialogue with the theoretical framework, on the empirical data and the context of this work. It is concluded that the social sports project has good intentions, however, the objectives are not effectively achieved as their idealizers point out. There is relevance for these children and young people with regard to the promotion of momentary physical and social well-being instead of promoting the citizenship of the participants.